Determining the Waist Circumference Cut off which Best Predicts the Metabolic Syndrome components in urban Africans: The SABPA study - Prinsloo, J.; Malan, L.; de Ridder, J. H.; Potgieter, J. C.; Steyn, H. S. (Experimental and Clinical Endocrinology & Diabetes, 2011)
Various studies have shown that the relationship between waist circumference (WC) and abdominal obesity is age, gender as well as ethnicity-dependent. WC criteria for Sub Saharan Africans have not been defined by the International Diabetes Federation (IDF). The aim was to determine which WC cut off best predicted Metabolic Syndrome (MetS) in a group of urban African teachers (80 males and 93 females). We determined sphygmomanometer blood pressure, WC, glucose, high density lipoprotein cholesterol (HdL) and triglyceride (TRIG) values. The males′ MetS profile was less favourable as their glucose, TRIG and blood pressure levels were higher than the proposed cut off for MetS. The females could be classified as obese, based on their mean BMI (32.78±6.36) and WC (93.48±15.68). Receiver operating characteristic (ROC) WC cut offs of 90, 91, 94 and 96 cm for the respective MetS components in males (blood pressure, HdL, glucose and TRIG) were suggested. In the females, cut offs of 92, 98, 94 and 94 cm for TRIG, blood pressure, HdL and glucose respectively, were put forward. Odds ratios revealed that increased blood pressure best predicted ROC WC in both males (OR 9.59; 95% CI 3.14–29.32) and females (OR 3.11; 95% CI 1.30–7.42) irrespective of age. We suggest that the optimal cut off point for the males be set at 90 cm, as opposed to the current 94 cm; whilst the female cut off be set at 98 cm as opposed to the existing cut off of 80 cm. Larger sample groups are recommended to justify our data.
Keywords: metabolic syndrome; central obesity; Setswana; black Africans; ROC